Technical service platform planning based on a company's competitive advantage and future market trends: A case study of an IC foundry. (September 2016) - Chiu, Ming-Chuan; Chiou, Jr-Yi
Highlights: Proposed technical service platform can assist in developing innovative services. Enterprises can extend company strength to obtain future technology leadership. This framework also provide feasible alternatives for future uncertainties. Abstract: Developing a unique competitive advantage while simultaneously complying with future trends has emerged as a solid strategy for securing a leading technology production position in the global marketplace. Prior studies have suggested the development of a framework for analyzing technical service platforms and valid conjoint methodologies. A reliable technical service platform planning can generate a variety of services to provide customers with many options and choices. Meanwhile, concurrent planning can enhance customer satisfaction by integrating diversified products and technologies. A multi-step approach is proposed to organize technological service platforms while incorporating corporate strengths and technological forecasting during platform development. In addition, scenario analysis is conducted as a decision support system for top managers. Therefore, enterprises can allocate resources in strategic planning so as to advance in the future. A case study of three-dimensional integrated circuit (3D-IC) technological service platform planning in the semiconductor industry demonstrates the advantages of the proposed methodology. We evaluated six alternatives to ensure the compliance of our research with market demands. Results show our method can enable enterprises to address both existing and potential customer requirements, develop more innovative services that meet different market segments, and achieve economy of scale. We show how decision makers can determine feasible alternatives while using scenario analysis to offer solutions in the future under uncertainty. Using our method, company strengths can be extended well in the future through this integration of design and forecasting.